Penerapan Non-Corporal Punishment di Madrasah Aliyah: Studi Kasus di MAN 1 Sungai Penuh dan MAN Kemantan Kerinci - Wanto, Deri; Idi, Abdullah; Jamin, Ahmad (BELAJEA: Jurnal Pendidikan Islam, 2018)
This article aims to examine and analyze non-corporal punishment in the character development of Madrasah Aliyah students in Jambi province. This research applied case study approach with purposive sampling technique. The data were collected by observing, interviewing, and documentating. The result showed that the application of non-corporal punishment works well in Madrasah Aliyah of Jambi province, student character can also be formed from non-corporal punishment contribution. The indicators could be seen by; (1) there is a change in the process of learning when the teacher implements non-corporal punishment, and the non-corporal punishment implementation in extracurricular activities goes well, (2) student character such as discipline can be developed with non-corporal punishment more obedient to madrasah regulations, and discipline enforcement by non-corporal punishment raises awareness and motivation of students who can improve their academic performance, (3) while the supporting factor of non-corporal punishment implementation in Madrasah Aliyah is cooperation of all elements of madrasah (headmasters, classteachers, teachers, janitor, security, and parents), while those that hinder the application of non-corporal punishment is a team that should always be supervised, full teacher activities, the teachers who do not care about the discipline, the distance of student residence to school, and financing.